Building on strengths in Naujaat: the process of engaging Inuit youth in suicide prevention - Anang, Polina; Naujaat Elder, Elizabeth Haqpi; Gordon, Ellen; Gottlieb, Nora Dalia; Bronson, Maria (International Journal of Circumpolar Health, 2019)
Anang P, Naujaat Elder EH, Gordon E, Gottlieb ND, Bronson M. Building on strengths in Naujaat: the process of engaging Inuit youth in suicide prevention. International Journal of Circumpolar Health . 2019;78(2): 1508321.